Impact of Custom and usage on implementations of Rules: In light of Book Al-Hidaya: عرف وعادت کے تغیر کے باعث احکام میں تغیر کا جائزہ: کتاب الہدایہ کی روشنی میں - Shahbaz, Muhammad Asim; Younus, Dr. Rizwan; Rehman, Hafiz u (Al-Aijaz Research Journal of Islamic Studies & Humanities, 2021)
Sharia’h has flexibility to resolve the emerging individual and communal problems. It has a rich jurisprudential literature concerning custom and usage. Islamic law placed the rule of custom within the sources of legislation. Muslim jurists explored the flexibility of divine text in light of community issues. The implementation of rules (Ahkam) has changed, and so have the interpretations. "Al-Hidaya" is the well-acknowledged jurisprudential code in the Muslim world. The ancient Muslim scholars, particularly the Hanafi School, always followed the principle of URF-O-ADAT (custom). The study at hand will examine the exercise of this principle in this book. It will review alterations to rules caused by the customary change. This article will explore the provisions of this book holding this principle. It will denote the criteria of application of the principle of usage in the implementation of rules. This research will demonstrate the significance of this jurisprudential approach to contemporary issues. It will make recommendations to bring legislation to address contemporary needs